Application of Rosemary and Eucalyptus Essential Oils on the Preservation of Cucumber Fruit - Xylia, Panayiota; Chrysargyris, Antonios; Shahwar, Durray; Ahmed, Zienab F.R.; Tzortzakis, Nikos G. (My University, 2022)
Cucumber (Cucumis sativus L.) is one of the most significant and frequently produced vegetable crops. However, because of its high perishability, keeping its quality from the farm to the market is a challenging problem. Various techniques have been employed to reduce postharvest losses and to extend the shelf life of vegetables and fruits. Recently, another approach is the application of eco-friendly elicitors as essential oils-EOs to prevent fruit decay and enhance its quality. Therefore, the purpose of this study was to assess the effectiveness of an environmentally friendly product (EP) based on rosemary and eucalyptus essential oils and two distinct application techniques (vapor and dipping) on maintaining quality characteristics of cucumber fruits during storage at 11 °C and ~90% relative humidity (RH) for two weeks. The results showed that the EP was successful in preserving cucumber fruit quality. Vaporized cucumbers did not show any significant weight losses, whereas dipped cucumbers showed a greater weight loss at 0.4% EP (3.5%) compared with the control (3%). Fruit treated with EP (vapor or dipping) or chlorine maintained firmness and ripening index during storage. Total soluble solids (TSS) levels were similar in all vapor-treated fruit while dipping application of chlorine increased TSS (4 oBrix) after 7 days of storage. Vapor or dipping application of EP or chlorine had a slight effect on cucumber color. Vaporized (EP or chlorine) cucumbers had comparable total phenols and antioxidant activity when compared with the control treatment, while dipped fruit had lower total phenols content and antioxidant activity at 0.8% EP after 7 days of storage. These findings indicate that the evaluated EP (vapor or dipping) can be a potential natural alternative to be used to preserve fresh produce instead of the common sanitizing agent (chlorine). Nevertheless, the application method and conditions should be further optimized for every product.
Keywords: Cucumber; Eco-friendly product; Quality preservation; Essential oils; Antioxidants